PENGEMBANGAN KEMITRAAN KA WASAN MATEMATIKA(MATH MASTER ZONE) DI KECAMATAN SA WAHAN KABUP ATEN NGANJUK - Muhtadi Muhtadi; Sutama Sutama; Sofyan Anif; Harun Joko Prayitno (Universitas Muhammadiyah Surakarta, 2015)
PEMITRA service activities in the kecamatan Sawahan kabupaten Nganjuk, had conducted educational activities, training, and mentoring for elementary school teachers, principals, supervisors and the person in charge of Math Masters Zone program to improve the basic concepts of mathematics and its teaching method. In this Pemitra conducted training activities learning methods of Math Masters, so that teachers had an understanding and basic mathematical concepts were true, and instructed it so easy and fun to their students. In the implementation of this Pemitra service activities, had given results and achievements were very enjoyable because math test scores elementary school students in the kecamatan Sawahan on the 2013/2014 school year had average to 8.5 and the highest value reached 10.0. Math Olympiad activities also quite lively, as students becomed more enthusiastic andexcited. Based on indicators of progress and this proves that the method Math Master who had been introduced by the Executive Team Pemitra, had helped to solve problems Numeric Phobia for elementary school students in the kecamatan Sawahan. Mathematics was considered subjects which so easy and very fun by the students.Constraints and problems still be faced today is the support and consistency of Nganjuk government has not been consistent in developing subdistrict Sawahan as Math Master Zone.